Halal Label On Food Products By Mui (Indonesian Ulama Council) And Students Purchasing Decision Of Faculty Of Business And Economic Universitas Muhammadiyah Surakarta (Muhammadiyah University Press, 2018)
The boundary between hala>l and hara>m in human life is explained clearly by Quran and Sunnah as a form of Allah guardianship. MUI established LPOM as an institution to issue halal certificates on food products. Food products that have been certified will be labeled by MUI logo. Universitas Muhammadiyah Surakarta instills religious values to students and expects them to choose food products with consideration to hala>l and hara>m aspects. This study aims to find out how much understanding of Faculty of Economics & Business Students on halal food products and how much the influence of MUI Labelization on their decision purchase. The research used field research method and qualitative data. This study showed that 69.3% of students sample who generally have understood halal products and halal label of MUI have a major influence in determining their purchasing to select halal products. Faculty of Economiccs & Business students who have very good understanding on Halal Products in most cases reached 81.63% of total population.",